Old City : New Rumours - Book launch event - Gregson, Ian; Rumens, Carol (The University of Hull)
Many of the best poets now publishing have some kind of association with Hull. To celebrate Larkin 25, Ian Gregson and Carol Rumens have assembled an anthology which brings together poems by an impressive number of these writers. We celebrate continuity as well as new beginnings in the wonderful variety of poetry represented in Old City: New Rumours. As many as possible of the featured poets will be invited to give short readings this event. We predict it will be an occasion to be remembered and rumoured for many years to come.